2022
DOI: 10.3390/ijerph19106109
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Metabolic Syndrome and Study of Anthropometric, Clinical and Biological Characteristics in Peri- and Postmenopausal Women in the City of Ksar El Kebir (Northern Morocco)

Abstract: This study aimed to determine the frequency of metabolic syndrome and to identify its predictive factors in peri- and post-menopausal women in the city of Ksar El Kebir, in northern Morocco. A total of 373 peri- and post-menopausal women between 45 and 64 years old participated in the study. Metabolic syndrome was diagnosed according to the National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATP III) definition. Body mass index (BMI) was calculated to assess the degree of obesity in women; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
(73 reference statements)
1
3
0
Order By: Relevance
“…The mean BMI of 30.17 km/m 2 observed in our study agrees with studies that have found a higher incidence of endometrial abnormalities in women with obesity (11).…”
Section: Discussionsupporting
confidence: 92%
“…The mean BMI of 30.17 km/m 2 observed in our study agrees with studies that have found a higher incidence of endometrial abnormalities in women with obesity (11).…”
Section: Discussionsupporting
confidence: 92%
“…However, this correlation was not observed in males and younger females with MetS; this could be attributed to changes in hormonal secretion and loss of estrogen in menopause, which causes an accumulation of visceral fat, leading to abdominal obesity [79,80]. Abdominal obesity is responsible for insulin resistance and the development of MetS [81]. Another possible explanation for the observed discrepancy can be attributed to sampling size, particularly in men with MetS.…”
Section: Discussionmentioning
confidence: 93%
“…Changes in hormone levels lead to abnormalities in lipid metabolism with elevated serum total cholesterol, LDL cholesterol, apolipoproteins, and triglycerides, and decreased high-density lipoprotein cholesterol (HDL-C) [ 91 ]. Reduced energy expenditure due to reduced lipid oxidation and reduced leptin sensitivity in menopausal women [ 92 ]. Postmenopausal women have a lower gut microbiome diversity, slightly similar to that of men, and are involved in sex hormone retention.…”
Section: Discussionmentioning
confidence: 99%